Anaesthetic efficacy of periodontal ligament injection of 2% lidocaine with 1:80,000 adrenaline - Shehab A Hamad (University of Mosul, College of Dentistry, 2006)
Abstract Aim: To evaluate the effectiveness of periodontal ligament injection of 2% lidocaine with 1:80,000 adrenaline in producing profound pulp anaesthesia and soft tissue anaesthesia. Materials and Methods: The sample of this study included 120 dental students, 72 males and 48 females, ranging in age from 18 to 23 years. The periodontal injection was administered to the periodontal space on the mesial and distal aspects of the central incisor, first premolar and first molar of both arches. The injection was administered by a standard dental syringe using 0.2 ml of 2% lidocaine with 1:80,000 adrenaline. The pulp anaesthesia was evaluated by electric pulp tester and soft tissue anaesthesia was evaluated by probing. Results: The success rate of pulp anaesthesia in this study was 57.5% (60% in the maxilla and 55% in the mandible). In both arches, first premolar and first molar teeth showed a significantly higher success rate than that of central incisor (p<0.05). The mesial and distal teeth, adjacent to the injected tooth, were anaesthetized in 29.7% and 40.8% respectively. No significant difference was noted in the success rate of pulp anaesthesia between mesial and distal teeth (p>0.05). The duration of pulp anaesthesia was 18.34 minutes. The duration of pulp anaesthesia was significantly longer in the mandibular than maxillary teeth (p<0.05). The extent of associated soft tissue anaesthesia was 14.77mm on the labial (buccal) aspect and 11.18 mm on the lingual (palatal) aspect. No significant difference was noted, in both arches, in the extension of soft tissue anaesthesia on both aspects (p>0.05). Conclusion: The periodontal ligament injection anaesthesia has a higher success rate in premolars and molars as compared to incisors. The duration of pulp anaesthesia was 18.34 minutes. The extent of soft tissue anaesthesia was 14.77 mm on the labial aspect and 11.18 mm on the lingual aspect.